Good bet on rubber - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
This could be a good time to get back into natural rubber. Although prices fell 50% from 1996 to US$ 0.70/kg in 2001, a study published early in 2002 by the University of Amsterdam predicts that a rise in demand and prices in the mid-term...